The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0206327
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of brown hare (Lepus europaeus) support limited migration and translocation of Greek populations

Abstract: Numerous studies have shown that the phylogeography of many species, including European brown hare, has been affected by the climatic oscillations of the Pleistocene. During this period the Balkans acted as a major refugium offering habitable conditions for many species. However, few studies have focused on the specific role of the Greek peninsula in the phylogeographic history of species in this southernmost margin of Balkans. We, therefore analyzed a 528 bp fragment of the D-loop region of mitochondrial DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Data from a broad genetic analysis of L. europaeus specimens (n = 154) from mainland and island populations in Greece as well as captive-reared individuals (n = 110) were compared with existing sequences (n = 310, includes the 110 captive-reared individuals) retrieved from GenBank with the aim to create a pan-European analysis (Minoudi et al 2018). The results confirm the deviation of the phylogenetic tree into two clades, the Anatolian and the European.…”
Section: Geneticsmentioning
confidence: 70%
“…Data from a broad genetic analysis of L. europaeus specimens (n = 154) from mainland and island populations in Greece as well as captive-reared individuals (n = 110) were compared with existing sequences (n = 310, includes the 110 captive-reared individuals) retrieved from GenBank with the aim to create a pan-European analysis (Minoudi et al 2018). The results confirm the deviation of the phylogenetic tree into two clades, the Anatolian and the European.…”
Section: Geneticsmentioning
confidence: 70%
“…At the genome-wide level, the genetic diversity of Tolai hares based on SNPs was higher (Table 2) (π = 0.05926, He = 0.37412, Ho = 0.40226, PIC = 0.2974) than that of other reported species, including rabbits (PIC = 0.2-0.2281, He = 0.2511-0.2857, Ho = 0.3072-0.3418, (Ren et al, 2019), and Yarkand hares (π = 0.0655, He = 0.3130, Ho = 0.2852, PIC = 0.2543 (Ababaikeri et al, 2021). The estimated nucleotide diversity of Tolai hares (π = 0.0442) based on mtDNA was also relatively high compared to other Lepus taxa, such as brown hares (π D-LOOP = 0.030, (Minoudi et al, 2018), Yarkand hares (π D-LOOP = 0.033, π CYTB = 0.008, (Shan et al, 2011), and Italian hares (L. corsicanus, π D-LOOP = 0.018, (Pierpaoli et al, Frontiers in Genetics frontiersin.org 2003). These higher genetic diversity values indicated that Tolai hare populations evolved under long-term favorable environmental conditions and remained relatively stable and genetically variable (Pironon et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Unlike other species in Europe and eastern China, such as the Brown hare (Minoudi et al, 2018), Panda (Ailuropoda melanoleuca) (Zhao et al, 2013), and Lizards (Shinisaurus crocodilurus) (Xie et al, 2022), our comprehensive indexes of two markers showed that L. t. lehmanni population remained stable, even in the LGM (0.0265-0.019 MYA) (Clark et al, 2009;Liang et al, 2017). Other studies have shown that among the Tibetan Plateau species, population size did not decline in the LGM (Liang et al, 2017), implying that the geographical distribution of species and climate oscillation indeed play an important role in population history.…”
Section: The Complex Population History Of Tolai Hare Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to other fauna and flora taxa inhabiting the Western Palearctic, certain degrees of genetic variation can be observed and very often, individuals can be linked to certain populations or geographic areas. This is illustrated by recent studies on Brown Hares (Lepus europaeus) (Minoudi et al 2018), Stone Martins (Martes foina) (Tsoupas et al 2019), plus Balkan Mole (Talpa stankovici) and European Mole (Talpa europaea) (Tryfonopoulos et al 2010), which revealed that populations from the Balkans have region specific haplotypes. However, the Wild Cat (Felis silvestris) only shows five main geographic groups across the whole of Europe, with some populations hybridizing with domestic cats (Mattucci et al 2016).…”
Section: Phylogeographical Situation Of Western Palearctic Birdsmentioning
confidence: 89%